Foreign Capital Inflows, Domestic Savings, and Economic Growth: The Case of Algeria - Nid, Mohammed Tahar (2012)
Understanding the growth process is central to development economics. Analyzing and interpreting the determinants of growth, either the process has worked or failed in countries is ultimately an empirical issue. This study attempts to explain this issue not limited to the economic impact of FCI, domestic savings, and Interest rate on economic growth in Algeria but also on how they are related in a dynamic framework.The model for analysis was developed based on the Two Gaps economic growth model.The analysis of this relationship is based on annual time series data for the period of 1980-20 10. This study employs approaches in its estimation of the dynamic relationship vector error correction model and granger causality. The results show that domestic savings have a positive and significant effect, but foreign capital inflows are insignificant to Algeria's economic growth in the long run. Also, the interest rate has significant influence towards economic growth in Algeria in the long run, The insignificant impact of FCI on economic Growth in Algeria, Could be due to the fact that FCI in Algeria during the period of the study is quite small. The finding, particularly on interest rates and savings has some policy relevance at the macro development perspective.